A New Precision Minimally Invasive Method of Glial Scar Simulation in the Rat Spinal Cord Using Cryoapplication - Telegin, Georgii B.; Minakov, Alexey N.; Chernov, Aleksandr S.; Kazakov, Vitaly A.; Kalabina, Elena A.; Manskikh, Vasily N.; Asyutin, Dmitry S.; Belogurov, Alexey A.; Gabibov, Alexander G.; Konovalov, Nikolay A.; Spallone, Aldo (Frontiers in Surgery, 2021)
According to the WHO, every year worldwide up to 500,000 people suffer a spinal cord injury (SCI). Various animal biomodels are essential for searching for novel protocols and therapeutic approaches for SCI treatment. We have developed an original model of post-traumatic spinal cord glial scarring in rats through cryoapplication. With this method the low-temperature liquid nitrogen is used for the cryodestruction of the spinal cord tissue. Forty-five Sprague Dawley (SD) male rats of the Specific-pathogen-free (SPF) category were included in this study. A Th13 unilateral hemilaminectomy was performed with dental burr. A specifically designed cryogenic probe was applied to the spinal cord for one minute through the created bone defect. The animals were euthanized at different time points ranging from 1 to 60 days after cold-induced injury. Their Th12-L1 vertebrae with the injured spinal cord region were removed “en bloc” for histological examination. Our data demonstrate that cryoapplication producing a topical cooling around -20°C, caused a highly standardized transmural lesion of the spinal cord in the dorsoventral direction. The lesion had an “hour-glass” shape on histological sections. During the entire study period (days 1-60), the necrotic processes and the development of the glial scar (lesion evolution) were contained in the surgically approached vertebral space (Th13). Unlike other known experimental methods of SCI simulation (compression, contusion, etc.), the proposed technique is characterized by minimal invasiveness, high precision, and reproducibility. Also, histological findings, lesion size, and postoperative clinical course varied only slightly between different animals. An original design of the cryoprobe used in the study played a primary role in the achieving of these results. The spinal cord lesion’s detailed functional morphology is described at different time points (1-60 days) after the produced cryoinjury. Also, changes in the number of macrophages at distinct time points, neoangiogenesis and the formation of the glial scar’s fibrous component, including morphodynamic characteristics of its evolution, are analyzed. The proposed method of cryoapplication for inducing reproducible glial scars could facilitate a better understanding of the self-recovery processes in the damaged spinal cord. It would be evidently helpful for finding innovative approaches to the SCI treatment.